2008
DOI: 10.4049/jimmunol.180.2.1040
|View full text |Cite
|
Sign up to set email alerts
|

The NF-κB Canonical Pathway Is Involved in the Control of the Exonucleolytic Processing of Coding Ends during V(D)J Recombination

Abstract: V(D)J recombination is essential to produce an Ig repertoire with a large range of Ag specificities. Although NF-κB-binding sites are present in the human and mouse IgH, Igκ, and Igλ enhancer modules and RAG expression is controlled by NF-κB, it is not known whether NF-κB regulates V(D)J recombination mechanisms after RAG-mediated dsDNA breaks. To clarify the involvement of NF-κB in human V(D)J recombination, we amplified Ig gene rearrangements from individual peripheral B cells of patients with X-linked anhid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 68 publications
1
6
0
Order By: Relevance
“…Recruitment of CtIP by BRCA1 is necessary for HR but not error-prone NHEJ shifting the balance of DSB repair to HR (26). Notably, Souto-Carneiro et al (40) found that NF-κB is involved in controlling the exonucleolytic activity on the coding ends during V(D)J recombination, whereby the authors excluded an influence of NF-κB on terminal deoxynucleotide transferase, Artemis and DNA-PKcs.…”
Section: Discussionmentioning
confidence: 99%
“…Recruitment of CtIP by BRCA1 is necessary for HR but not error-prone NHEJ shifting the balance of DSB repair to HR (26). Notably, Souto-Carneiro et al (40) found that NF-κB is involved in controlling the exonucleolytic activity on the coding ends during V(D)J recombination, whereby the authors excluded an influence of NF-κB on terminal deoxynucleotide transferase, Artemis and DNA-PKcs.…”
Section: Discussionmentioning
confidence: 99%
“…To gain further insight into the mechanisms that shape the xenomouse repertoire, CDRH3 and D-JH pairing in the nonproductive repertoire were analyzed. Developing human B cells may undergo repetitive rounds of D to JH recombination between the common lymphoid precursor and the pre-B cell stage before a final DJH recombination occurs (38). This process is evident in the significantly increased use of distal D genes with JH5 and JH6 segments in the healthy donor B cells (p = 0.003) (Fig.…”
Section: Xenomouse Rearrangements Have a Locus Positional Bias In D-jmentioning
confidence: 99%
“…Thus, whereas in WT cells the frequency of P-additions is similar at DJ H and V H D, in Fanca −/− cells we found 3 times more P-additions at DJ H than at V H D junctions. An elevated frequency of sequences with P-additions, but at both DJ H and V H D junctions, was previously reported in X- linked anhidrotic ectodermal dysplasia with hyper-IgM syndrome (HED-ID), a rare pathology due to a genetic determined deficiency in NF-kB activation29. In HED-ID exacerbated P-nucleotide additions have been directly associated to an altered exonucleolytic processing of the coding ends.…”
Section: Discussionmentioning
confidence: 73%